Sistem Pakar menggunakan Metode Forward Chaining untuk Diagnosa Penyakit Tanaman Padi berbasis Android - Endra, Robby Yuli; Antika, Ayu (Jurnal Informatika Universitas Pamulang, 2021)
The majority of the people in Labuhan Ratu VIII Village, Labuhan Ratu District, East Lampung Regency work as farmers, especially rice farmers. The inhibiting factor for production in this village is a disease that attacks plants during the growing season so that it becomes the main problem in this study. The main purpose of this research is to build an expert system application to help farmers solve farmer problems in diagnosing rice plant diseases based on Android. The data used in this study consisted of 7 diseases in rice plants, namely tungro, bacterial leaf blight (HDB), stem rot, midrib rot, blast, grass dwarf and leaf midrib blight. The method used in this research is the Forward Chaining Method. The method used to build an expert system application, the tracking process of this method is from the data, then match the data with the IF part of the IF-THEN rules. If it is in accordance with the existing rules, then the rules will be executed to get a conclusion. The results of this study, the application of an expert system using Forward chaining can be used to diagnose rice plant diseases with several steps, namely selecting symptoms, conducting consultations, and displaying the results of the consultation.